Efforts to Improve Student Learning Outcomes in Qur'an Hadith Learning at MI Tarbiyatul Aulad - Khoerun Nida; Khitoh Khoeriyah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the quantity and quality of students. In the learning process, the selection of the right learning method greatly affects the high and low learning outcomes of students. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were 17 students in grade 5 at MI Tarbiyatul Aulad Kaliloka Sirampog Brebes. Classroom action research was carried out in two cycles. The data for this study were obtained using test techniques and non-test techniques. The data analysis techniques used in this study were documents, tests and observations. The results of the study showed that the average learning outcomes of students increased. It is known that the KKM value that has been determined by the school is 77. In the pre-study, it was known that 17 students had not completed 10 and 7 students had completed. In cycle I, there was an increase of 11 students who completed with a percentage of 65% and 6 students who had not completed with a percentage of 35%. Furthermore, in cycle II there was an increase of 15% of students completing 11 with a percentage of 80% and 6 students who had not completed with a percentage of 20%. Thus, the strategy can improve student learning outcomes in the subject of Al Qur'an Hadith Learning outcomes material for short letters in the Qur'an.